Acral melanoma after a bitumen burn - Peila, R... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1999)
A case of acral melanoma developed in a 59-year-old-man; it was diagnosed 45 days after a bitumen burn had been reported. The relationship between the bitumen burn and the development of the malignant melanoma is discussed.
Keywords: Burns, chemical; Complications; Heel; Melanoma; Middle age